Topology-Inspired Method Recovers Obfuscated Term Information From Induced Software Call-Stacks - Maggs, Kelly; Robins, Vanessa (Frontiers in Applied Mathematics and Statistics, 2021)
Fuzzing is a systematic large-scale search for software vulnerabilities achieved by feeding a sequence of randomly mutated input files to the program of interest with the goal being to induce a crash. The information about inputs, software execution traces, and induced call stacks (crashes) can be used to pinpoint and fix errors in the code or exploited as a means to damage an adversary’s computer software. In black box fuzzing, the primary unit of information is the call stack: a list of nested function calls and line numbers that report what the code was executing at the time it crashed. The source code is not always available in practice, and in some situations even the function names are deliberately obfuscated (i.e., removed or given generic names). We define a topological object called the call-stack topology to capture the relationships between module names, function names and line numbers in a set of call stacks obtained via black-box fuzzing. In a proof-of-concept study, we show that structural properties of this object in combination with two elementary heuristics allow us to build a logistic regression model to predict the locations of distinct function names over a set of call stacks. We show that this model can extract function name locations with around 80% precision in data obtained from fuzzing studies of various linux programs. This has the potential to benefit software vulnerability experts by increasing their ability to read and compare call stacks more efficiently.